Towards a functional definition of innovation for Malaysian Universities. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2015)
The landscape of higher education has been so greatly transformed that public universities are now perceived by the public, corporate and political leaders as key components in a national scientific and technological innovation system.